Film in Canada - Leach, Jim (Oxford Univ. Press, 2006)
"Film in Canada offers a comprehensive examination of Canadian cinema in its political and cultural contexts. While highlighting the films and filmmakers that have defined the national industry since the 1960s, this book also looks at many of the factors that have influenced Canadian filmmaking, including Canada's ethnic and linguistic diversity, the country's national identity, and the emergence of a global media marketplace. Each chapter explores both historical trends and contemporary examples of a specific topic, allowing the chapters to be used in sequence or independently. With careful annotations, a detailed filmography and bibliography, and a ten-page insert of film stills, this book is ideal for students of Canadian film or of Canadian arts and culture generally."--BOOK JACKET.